2013
DOI: 10.2146/ajhp120363
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic effectiveness and safety of aprepitant in patients with hematologic malignancy receiving multiday chemotherapy

Abstract: The addition of aprepitant to granisetron increased the antiemetic effect without influencing ADEs in patients treated with moderately to highly emetogenic multiday chemotherapy for hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Recently, we reported that the addition of aprepitant to granisetron improved antiemetic control without influencing AdEs in patients with hematologic malignancies receiving multiday conventional chemotherapy. 21) In the present study, the frequencies of AdEs in the control and aprepitant groups were similar. Based on these results, aprepitant can be safely Table 1.…”
Section: -18)supporting
confidence: 64%
See 1 more Smart Citation
“…Recently, we reported that the addition of aprepitant to granisetron improved antiemetic control without influencing AdEs in patients with hematologic malignancies receiving multiday conventional chemotherapy. 21) In the present study, the frequencies of AdEs in the control and aprepitant groups were similar. Based on these results, aprepitant can be safely Table 1.…”
Section: -18)supporting
confidence: 64%
“…At our institution, pharmacists and physicians had discussed the antiemetic treatment for the patients with hematologic malignancies, and introduced aprepitant to conventional chemotherapies 21) as well as preparative regimens for HSCT since April 2010. In this study, we retrospectively evaluated the antiemetic effect and safety of aprepitant in combination with 5-HT 3 receptor antagonist in such patients undergoing autologous peripheral blood stem cell transplantation (auto-PBSCT).…”
mentioning
confidence: 99%
“…Although the agent cytarabine when administered at a dose of greater than 1 g/m 2 is currently classified as having a moderate emetogenic potential, recent data indicate that regimens containing a cytarabine dose of ≥4 g/m 2 per day should be considered as highly emetogenic [14,[22][23][24]. In a recent trial, two extended schedules of palonosetron from day 1 to day 5 or on days 1, 3 and 5, were randomly compared with daily ondansetron in patients with acute myelogenous leukemia or high-risk myelodysplastic syndrome treated with regimens containing high-dose cytarabine (12 g/m 2 for 3 days or 30 mg/m 2 for 5 days) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in chemotherapy patients, both large and small, showed that addition of aprepitant to standard antiemetic regimens led to significant improvements in nausea and vomiting [74,75]. It has subsequently been adopted by gastroenterologists for off-label use in patients with gastroparesis.…”
Section: Neurokinin-1 Receptor Antagonistsmentioning
confidence: 99%